2009
DOI: 10.1038/ncb1831
|View full text |Cite
|
Sign up to set email alerts
|

CHD8 suppresses p53-mediated apoptosis through histone H1 recruitment during early embryogenesis

Abstract: The chromodomain helicase DNA-binding (CHD) family of enzymes is thought to regulate gene expression, but their role in the regulation of specific genes has been unclear. Here we show that CHD8 is expressed at a high level during early embryogenesis and prevents apoptosis mediated by the tumour suppressor protein p53. CHD8 was found to bind to p53 and to suppress its transactivation activity. CHD8 promoted the association of p53 and histone H1, forming a trimeric complex on chromatin that was required for inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
185
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(204 citation statements)
references
References 45 publications
19
185
0
Order By: Relevance
“…However, because it is possible to reliably identify low amounts of true interacting proteins by improving the signal-to-noise ratio in LC-MS/MS, we considered that reproducibly decreasing the level of nonspecific noise proteins in single-step purification samples would be a valid approach. Therefore, we empirically developed and optimized the conditions for sample preparation, and using this methodology, found more than fifty significant protein-protein interactions (Hirano et al, 2005;Kitajima et al, 2006;Iioka et al, 2007;Komatsu et al, 2007;Nishiyama et al, 2009;Kaneko et al, 2009;Komatsu et al, 2010). In spite of this useful methodology, we realized the limitations of the existing preparation method in large-scale analysis, because we found that the amount of true interactors, as well as nonspecific proteins, in manually parallel-prepared samples varied.…”
Section: Discussionmentioning
confidence: 99%
“…However, because it is possible to reliably identify low amounts of true interacting proteins by improving the signal-to-noise ratio in LC-MS/MS, we considered that reproducibly decreasing the level of nonspecific noise proteins in single-step purification samples would be a valid approach. Therefore, we empirically developed and optimized the conditions for sample preparation, and using this methodology, found more than fifty significant protein-protein interactions (Hirano et al, 2005;Kitajima et al, 2006;Iioka et al, 2007;Komatsu et al, 2007;Nishiyama et al, 2009;Kaneko et al, 2009;Komatsu et al, 2010). In spite of this useful methodology, we realized the limitations of the existing preparation method in large-scale analysis, because we found that the amount of true interactors, as well as nonspecific proteins, in manually parallel-prepared samples varied.…”
Section: Discussionmentioning
confidence: 99%
“…Other members of the CHD protein family have been implicated in proliferation and/or apoptosis (Bagchi et al, 2007;Gaspar-Maia et al, 2009;Nishiyama et al, 2009;Rodriguez-Paredes et al, 2009). In vitro inhibition of Chd1 creates abnormally high levels of neural differentiation, and is required for maintenance of pluripotency (Gaspar-Maia et al, 2009).…”
Section: Dosage Effects Of Chd7 In Neuroblast Developmentmentioning
confidence: 99%
“…In contrast to the rare isolated mutations in these three CHD genes, 13 different recurrent alleles of CHD8 have been observed in individuals with ASD/ID in association with macrocephaly and gastrointestinal disturbance [66,70,[75][76][77][78]. In cultured cells, CHD8 has been shown to bind CHD7 and to both bind and regulate p53 and inhibit its proapoptotic effects during development; thus, it is surprising that loss of CHD8 is not associated with broader phenotypic effects in humans [79][80][81][82]. Knockdown of Chd8 by shRNA does not alter the morphology or neural ectodermal markers of neural progenitors derived from human iPS cells, but does significantly impair their gene expression [74].…”
Section: Chd Proteins In Human Diseasementioning
confidence: 97%